COVID-19 induces more pronounced extracellular matrix deposition than other causes of ARDS - de Souza Xavier Costa, Natália; Ribeiro Júnior, Gabriel; do Nascimento, Ellen Caroline Toledo; de Brito, Jôse Mara; Antonangelo, Leila; Faria, Caroline Silvério; Monteiro, Jhonatas Sirino; Setubal, João Carlos; Pinho, João Renato Rebello; Pereira, Roberta Verciano; Seelaender, Marilia; de Castro, Gabriela Salim; et al. (Respiratory research, 2023)
Lung fibrosis is a major concern in severe COVID-19 patients undergoing mechanical ventilation (MV). Lung fibrosis frequency in post-COVID syndrome is highly variable and even if the risk is proportionally small, many patients could be affected. However, there is still no data on lung extracellular matrix (ECM) composition in severe COVID-19 and whether it is different from other aetiologies of ARDS. We have quantified different ECM elements and TGF-β expression in lung tissue of 28 fatal COVID-19 cases and compared to 27 patients that died of other causes of ARDS, divided according to MV duration (up to six days or seven days or more). In COVID-19 cases, ECM elements were correlated with lung transcriptomics and cytokines profile. We observed that COVID-19 cases presented significant increased deposition of collagen, fibronectin, versican, and TGF-β, and decreased decorin density when compared to non-COVID-19 cases of similar MV duration. TGF-β was precociously increased in COVID-19 patients with MV duration up to six days. Lung collagen was higher in women with COVID-19, with a transition of upregulated genes related to fibrillogenesis to collagen production and ECM disassembly along the MV course. Fatal COVID-19 is associated with an early TGF-β expression lung environment after the MV onset, followed by a disordered ECM assembly. This uncontrolled process resulted in a prominent collagen deposition when compared to other causes of ARDS. Our data provides pathological substrates to better understand the high prevalence of pulmonary abnormalities in patients surviving COVID-19.